Legal mechanisms for ensuring the effectiveness of customs control as a way to counteract customs torts - Moskaliuk, Nadiia; Kharchenko, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article is devoted to the study of legal mechanisms for ensuring the effectiveness of customs control as a key tool for combating customs torts in modern conditions. Customs control plays an important role in ensuring the economic security of the State, since its purpose is to protect national interests by preventing illegal movement of goods across the border, combating smuggling and customs duty evasion. The study includes an analysis of the legal provisions governing the activities of customs authorities, as well as a review of current international standards and recommendations on the organisation of customs control. The author examines the main problems that arise in the process of customs control, in particular, those related to the effectiveness of existing legislation, imperfection of administrative procedures and lack of proper cooperation between customs authorities of different countries. The author also highlights the issue of corruption, which significantly weakens the effectiveness of customs authorities and creates additional risks for the national economy. The article focuses on the need to introduce modern information technologies into the customs control process, such as electronic systems for processing customs declarations and automated risk management tools. This allows for a more accurate analysis and forecasting of the risks of customs offences and improves the transparency and accessibility of customs procedures. International legal instruments, such as the WCO Convention on the Simplification and Harmonisation of Customs Procedures, and their role in enhancing the effectiveness of customs control are also considered. The results of the study point to the need to improve the legal framework and introduce more effective control mechanisms at all stages of the customs process, in particular through the integration of innovative technologies, intensification of international cooperation and professional training of customs officers. Such measures will help to reduce the level of customs torts and ensure the stable functioning of the customs system as an important element of the economic security of the State.